The A2B Adenosine Receptor Modulates the Epithelial– Mesenchymal Transition through the Balance of cAMP/PKA and MAPK/ERK Pathway Activation in Human Epithelial Lung Cells - Giacomelli, Chiara; Daniele, Simona; Romei, Chiara; Tavanti, Laura; Neri, Tommaso; Piano, Ilaria; Celi, Alessandro; Martini, Claudia; Trincavelli, Maria L. (Frontiers in Pharmacology, 2018)
The epithelial-mesenchymal transition (EMT) is a complex process in which cell phenotype switches from the epithelial to mesenchymal one. The deregulations of this process have been related with the occurrence of different diseases such as lung cancer and fibrosis. In the last decade, several efforts have been devoted in understanding the mechanisms that trigger and sustain this transition process. Adenosine is a purinergic signaling molecule that has been involved in the onset and progression of chronic lung diseases and cancer through the A2B adenosine receptor subtype activation, too. However, the relationship between A2BAR and EMT has not been investigated, yet. Herein, the A2BAR characterization was carried out in human epithelial lung cells. Moreover, the effects of receptor activation on EMT were investigated in the absence and presence of transforming growth factor-beta (TGF-β1), which has been known to promote the transition. The A2BAR activation alone decreased and increased the expression of epithelial markers (E-cadherin) and the mesenchymal one (Vimentin, N-cadherin), respectively, nevertheless a complete EMT was not observed. Surprisingly, the receptor activation counteracted the EMT induced by TGF-β1. Several intracellular pathways regulate the EMT: high levels of cAMP and ERK1/2 phosphorylation has been demonstrated to counteract and promote the transition, respectively. The A2BAR stimulation was able to modulated these two pathways, cAMP/PKA and MAPK/ERK, shifting the fine balance towards activation or inhibition of EMT. In fact, using a selective PKA inhibitor, which blocks the cAMP pathway, the A2BAR-mediated EMT promotion were exacerbated, and conversely the selective inhibition of MAPK/ERK counteracted the receptor-induced transition. These results highlighted the A2BAR as one of the receptors involved in the modulation of EMT process. Nevertheless its activation is not enough to trigger a complete transition, its ability to affect different intracellular pathways could represent a mechanism at the basis of EMT maintenance/inhibition based on the extracellular microenvironment. Despite further investigations are needed, herein for the first time the A2BAR has been related to the EMT process, and therefore to the different EMT-related pathologies.